2010
DOI: 10.1021/es101003j
|View full text |Cite
|
Sign up to set email alerts
|

Redox Control and Hydrogen Production in Sediment Caps Using Carbon Cloth Electrodes

Abstract: Sediment caps that degrade contaminants can improve their ability to contain contaminants relative to sand and sorbent-amended caps, but few methods to enhance contaminant degradation in sediment caps are available. The objective of this study was to determine if, carbon electrodes emplaced within a sediment cap at poised potential could create a redox gradient and provide electron donor for the potential degradation of contaminants. In a simulated sediment cap overlying sediment from the Anacostia River (Wash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Data from this study will enable better design of reactive sediment caps, 6 electrode-based remedial approaches, 25 and energy generation from environmentally-deployed electrodes. 2628 …”
Section: Introductionmentioning
confidence: 99%
“…Data from this study will enable better design of reactive sediment caps, 6 electrode-based remedial approaches, 25 and energy generation from environmentally-deployed electrodes. 2628 …”
Section: Introductionmentioning
confidence: 99%
“…It was expected that siderite and calcite would provide long term pH buffering capacity while bicarbonate would provide short term pH buffering capacity. Studies had previously shown that an unbuffered system would exhibit pH excursions which would hinder microbial community development (Sun et al, 2010). The pH in the control cap system was stable without buffering.…”
Section: Methodsmentioning
confidence: 99%
“…A technology for a continuous introduction of electron acceptors and providing conditions conducive to hydrocarbon oxidation has limited bioremediation of PAH contaminated sediments. Using an electric current may be an alternative option for supplying more favorable electron acceptors and conditions, providing a potentially viable remedial approach (Strycharz et al, 2008; Aulenta et al, 2009; Sun et al, 2010; Zhang et al, 2010; Chun et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…This conceptual model could be exploited to augment sand-based caps with organic carbon (i.e., electron donor) to promote and sustain microbial activity in the cap. A more aggressive approach has been proposed by Sun et al (2010) who investigated the use of electrodes within a bench-scale cap to supply both hydrogen (electron donor) and oxygen (electron acceptor). The idea is intriguing since the electrodes could supply a stable source of electron donor within the cap to support reductive biotransformations and also provide oxygen to artificially create a sequenced anaerobic to aerobic treatment approach, which would be advantageous for the treatment of PCBs and chlorinated solvents.…”
Section: In Situ Cappingmentioning
confidence: 99%